Dengue and Zika flaviviruses in bats - Aréchiga-Ceballos, Nidia; Rendón-Franco, Emilio; Muñoz-García, Claudia I.; Olave-Leyva, Ignacio; Aguilar-Setién, Alvaro (Therya Notes, 2024)
Bats are natural reservoir hosts of a diverse viruses that affect humans. However, the role of bats as reservoirs for dengue (DENV) and Zika (ZIKV) flaviviruses is still controversial. Molecular and serological detection in several species suggests receptivity. Backwards, other works suggest that chiropters are not receptive as no antibodies or viruses were detected. This review examines the controversy, analyzing laboratory and field studies and 4 publications about the experimental infection of Artibeus sp. bats with DENV and ZIKV. Contradictory reports about the susceptibility of chiropter cell lines to replicate DENV may be due to the phylogenetically divergent origin of cells used, as in a study reporting viral production, proceeds from Old World bats (Megachiroptera) and in studies reporting not viral production, proceeds from neotropical bats (Yangochiroptera). Serological contradictory reports may be due to the used tests. The most accurate test is the Sero-Neutralization Test (SNT). Reports using Hemagglutination Inhibition (HIT) or Enzyme-Linked Immunosorbent Assay (ELISA) could give false positives. Thereby, all 4 experimental infections analyzed, used neotropical (Yangochiroptera) Artibeus sp. bats, and all reported defective or no replication of both flaviviruses by RT-PCR reference test. Considering SNT as a gold standard, no seroconversion was found. However, histopathological alterations were reported in organs of experimentally infected bats with both flaviviruses. These results suggest that bats of the genus Artibeus sp. are not efficient amplifiers or reservoirs of DENV or ZIKV. Nevertheless, both human flavivirus could cause alterations. Other bat species need to be studied.